Directive Speech Acts In Trilingual Students' Classroom Interactions At Pondok Modern Al-Aqsha - Wulan Sri Ratna Diva Pratiwi; Cipto Wardoyo; Agry Pramita (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
The evolution of Indonesian Islamic boarding schools (pesantren) toward a trilingual education model (Arabic, English, and Indonesian) has created a complex communicative landscape in which directive speech acts serve as a primary pedagogical tool. This study aims to: (1) identify the types of directive speech acts employed in trilingual classroom interactions at Pondok Modern Al-Aqsha; (2) analyze their pragmatic functions in teacher-student and student-student interactions; and (3) examine how these functions differ between Arabic-dominant Islamic studies lessons and Indonesian/English-dominant general education lessons. Adopting a qualitative descriptive approach with a sociopragmatic lens, data were collected from 12 hours of non-participant observations, audio-visual recordings, and semi-structured interviews with three subject teachers and approximately 90 junior high school students (Grades 7–9) at Pondok Modern Al-Aqsha. Data were analyzed using Searle’s (1979) directive taxonomy and Miles and Huberman’s (1994) interactive flow model, with researcher triangulation and data source triangulation (inter-rater reliability: Cohen’s Kappa = 0.87) applied to ensure credibility. Seven directive types were identified commanding (38%), requesting (22%), suggesting (12%), inviting (10%), prohibiting (8%), begging (6%), and advising (4%) distributed unevenly across languages. Commands and prohibitions dominated Arabic-medium Islamic studies (42% of all directives), while requests, suggestions, and invitations predominated in English and Indonesian general education lessons (58%). Peer directives were genuinely trilingual, with Indonesian as the primary medium (61%). The study concludes that directive speech acts at Pondok Modern Al-Aqsha perform a “dual-identity” function, balancing traditional religious authority with modern pedagogical facilitation, demonstrating that pragmatic competence is essential for effective multilingual educational communication.